Beban kerja sebagai determinan utama keinginan berpindah di kalangan pegawai: Studi pada perusahaan BUMN di Semarang - Khasanah, Tri Uswatun; Perdana, Tito Aditya; Astuti, Sih Darmi; Aqmala, Diana (Nur Science Institute, 2025)
This study investigates the Influence of work environment, workload, and work stress on turnover intention among employees of a state-owned enterprise (BUMN) located in Semarang. Turnover intention reflects an employee's desire to voluntarily leave the organization, which can disrupt operational stability and productivity. A quantitative research design was adopted, using a survey of employees as respondents. Data were collected through structured questionnaires and analyzed using multiple linear regression. The empirical findings reveal that the work environment, workload, and work stress simultaneously exert a positive and significant effect on turnover intention. A less supportive work environment, excessive workload, and heightened stress levels were identified as key drivers influencing employees' intention to resign. Furthermore, these three variables collectively explain the variance in turnover intention. Based on these results, it is recommended that the company enhance its work environment, implement better workload management strategies, and provide effective stress management programs to minimize the risk of high employee turnover.